Unpacking U.S. and German Individual Bankruptcy Systems: Insights and Recommendations for Georgia - Managadze, Irakli (Journal of Law, 2024)
I want to thank Professor Tibor Tajti (Central European University) for his invaluable guidance and support during my research. Also, I extend my appreciation to Emeritus Professor Reinhard Bork (Hamburg University) for his insights into the German consumer insolvency system. The article addresses the absence of individual bankruptcy law in Georgia, despite the growing need arising from increased credit accessibility and subsequent default rates. The central research question revolves around an in-depth examination of individual bankruptcy frameworks in the United States (U.S.) and Germany. Drawing from these jurisdictions, this article offers recommendations to inform Georgian lawmakers on key policies, regulations, and features to consider when instituting provisions for individual bankruptcy. Furthermore, insights gained from an interview with Emeritus Professor Reinhard Bork, a distinguished authority on German insolvency law, enrich the discourse on the practical issues of the German consumer insolvency system.